Accelerating digital transformation through digital leadership: strategies for innovation, sustainability, and organisational performance enhancement - Nasrun, Muhammad Kahfi; Susilo, Heru; Afrianty, Tri Wulida (Universitas Negeri Surabaya, Indonesia, 2025)
This study aims to explore how digital leadership accelerates the adoption of disruptive technologies, supports green innovation, and integrates digital transformation with hybrid work models to enhance organisational performance and employee well-being. Utilising a systematic literature review (SLR) approach and analysing 59 open-access articles from the Scopus database, this study identifies key trends in digital leadership literature. The findings show that digital leadership has gained increasing attention since 2021, particularly in the areas of business innovation, organisational resilience, and digital transformation. Major academic contributions come from Indonesia, Germany, and Malaysia. The adoption of AI and blockchain strengthens the effectiveness of digital leadership through data-driven decision-making, operational efficiency, and enhanced transparency. Furthermore, digital leadership promotes green innovation and sustainable business strategies while improving productivity and work-life balance through hybrid work models. The implications of these findings suggest that digital leadership is a key element in guiding organisations to adopt disruptive technologies, introduce green innovations, and design flexible work models. Organisations must develop adaptive, innovative, and technology-driven leadership to remain competitive and sustainable in the digital era.